Dylematy związane z interpretacją pojęcia efektywności a obecne uwarunkowania działania przedsiębiorstwa - Różański, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This paper concentrates on analysis of links between: - effectiveness and proprietory form of enterprise, - effectiveness and features of evolution of enterprise in postindustrial era, - effectiveness and new ideas in the field of business management. Changes inside of enterprise and changes of environment limit usefulness of traditional meaning of effectiveness. That is why is needed complex of understanding of effectiveness in current conditions of activity of enterprise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 426-432